Researching the far right : theory, method and practice - Ashe, Stephen D. HerausgeberIn; Busher, Joel HerausgeberIn; Macklin, Graham HerausgeberIn; Winter, Aaron HerausgeberIn (Routledge studies in fascism and the far right, 2021)
"Researching the Far Right brings together researchers from across the humanities and social sciences to provide much needed discussion about the methodological, ethical, political, personal, practical and professional issues and challenges that arise when researching far right parties, their electoral support, and far right protest movements. Drawing on original research focussing mainly on Europe and North America over the last thirty years, this volume explores in detail the opportunities and challenges associated with using ethnographic, interview-based, quantitative and online research methods to study the far right. These reflections are set within a wider discussion of the evolution of far right studies from a variety of disciplinary viewpoints within the humanities or the social sciences, tracing the key developments and debates that shape the field today. This volume will be essential reading for students and scholars with an interest in understanding the many manifestations of the far right and cognate movements today. It also offers insight and reflection that is likely to be valuable for a wider range of students and scholars across the humanities and social sciences who are carrying out work of an ethically, politically, personally, practically and professionally challenging nature"--